New ALMA constraints on the star-forming interstellar medium at low metallicity: a 50 pc view of the blue compact dwarf galaxy SBS 0335−052 - Cormier, Diane; Hony, Sacha; Glover, Simon; Klessen, Ralf S.; Bigiel, Frank (Monthly notices of the Royal Astronomical Society. Letters, 2017)
Abstract. Properties of the cold interstellar medium of low-metallicity galaxies are not well known due to the faintness and extremely small scale on which emi
Gesehen am 27.09.2018